(untitled) (European journal of volunteering and community-based projects, 2020)
Purpose: The aim of the paper is to highlight the role of third sector entities in the context of public interest networks. To carry out its activities, the public body often relies on entities belonging to the third sector, with which it enters into informal agreements or which generates or controls through financing or constitution with ad hoc statutory intervention. A complex governance structure is therefore created with the participation of different actors. Design/methodology/approach: The methodology used consists of an analysis of the business economic literature, aimed at identifying the characteristics of the public company and the growing complexity of public management. This complexity has led to the birth of New Public Governance, which goes beyond the sterile dichotomy of "administration against management" and which allows a more complete and integrated approach to the study and practice of Public Administration. Findings: New Public Governance, by addressing the issue of relations between the various Public Administrations and between Public Administration and private entities, favors forms of outsourcing and co-managing, leading to the development of inter-institutional cooperation, and the consequent creation of networks of interest public. The public interest networks, which include public companies and third sector entities, represent the result of a path of structural and organizational change aimed at pursuing the public interest. From this new system of relationships emerges the need for adequate programming, control and coordination systems, different from the traditional ones. Originality/value: the paper addresses the issue of governance of local authorities, using the innovative New Public Governance framework, intended as an evolution of the bureaucratic model and the New Public management.